Optimalisasi Penggunaan Gipsum dan Batu Kapur pada Pembuatan Semen Putih - Ahmad Riyanto; Devi Yuliani; Laeli Rizki Amalia; Erna Astuti (Universitas Ahmad Dahlan, 2019)
White Portland cement is a fine, gray or white powder, which consists of a mixture of hydraulic cement materials consisting mainly of calcium silicate, aluminate, and aluminoferrite. The manufacture of white portland cement requires special raw material requirements and manufacturing processes, such as raw materials containing very low iron oxides and manganese oxides. Various tests were carried out to obtain white cement of good quality and meet Indonesian National Standards or Standar Nasional Indonesia (SNI). The tests included raw material testing (Lost on Ignition test, LOI) on various compositions and LOI test, % SO3 test, and color test on white Portland cement. The results showed that the greater the % SO3, the strength of white Portland cement will decrease and the greater the LOI, the white Portland cement will be easily damaged. So from the results of the study obtained a good raw material composition for white Portland cement is 89% white slag, 4% limestone, and 7% gypsum. All test results meet Indonesian National Standards or SNI.